The Study of Hematological Profile in Preterm Low Birth Weight Neonates - Ghodake, Sonali Arun; Kulkarni, Aparna M; Jadhav, Rohini; Gudale, Neha; Eksambekar, Padmini; Jagdale, Vishakha; Ramteke, Ravindra (Annals of Pathology and Laboratory Medicine, 2025)
Background: Hematological parameters like Hemoglobin, WBC count, and Platelet count are used to evaluate complications of Preterm LBW neonates. These parameters are affected by factors like prematurity complications, late umbilical cord clamping. sample collection time. NS is associated with neutropenia and thrombocytopenia. PNA changes hematological parameters. RDS neonates have insufficient or dysfunctional surfactant leading to low oxygen levels and hypoxia, affecting hematological parameters. The study aims to determine the hematologic profile of preterm neonates in relation to these conditions. Methods: The study was conducted in a tertiary care center. This prospective observational study included all Preterm LBW neonates admitted in NICU. Laboratory investigation of CBC was done using automated Sysmex- XT-2000i counter. Results: A total of 638 preterm infants were included in this study who were admitted in NICU. All the patients CBC were determined. In this study, main causes for admission of preterm LBW neonates were NS, PNA, RDS and others (convulsions, Rh incompatibility, meningitis, pyloric stenosis, Downs syndrome). This study constitutes 58% (264) cases of NS, 23% (168) cases of PNA, 10% (126) cases of RDS and 9% (80) cases due to other causes. Conclusion: Routine haematological screening for preterm LBW neonates must be implemented, with special attention to the high risk cases of NS, PNA and RDS. Early identification and management of haematological abnormalities are crucial. Therefore, by enhancing our understanding and management of these conditions, we can significantly improve prognosis and quality of life for these neonates.